Protein C deficiency in a child with inferior vena cava thrombosis following abdominal trauma - H. Cherrabi; M.A. Oukhouya; F. Smahi; M.T. Melllouki; K.E.L. Ghazy; Y. Aznague; A. Boutaleb; H. Nassik; O. benlenda; A. Mekkaoui; S. Tiski; S. wakrim (Elsevier, 2022)
There are very few data in the literature describing the occurrence of venous thrombosis in children. This raises the essential problem of late diagnosis, especially in asymptomatic or pauci-symptomatic presentations where this pathology may be unrecognized.The post-traumatic context of venous thrombosis in children, reported in a few cases, should lead to the suspicion of thrombophilia and to a clinical, biological and radiological etiological assessment.We report in our work the observation of a 14-year-old girl admitted in the context of a polytrauma with minimal mechanism in whom the lesion assessment revealed an extensive thrombosis of the inferior vena cava in the supra renal area, with a review of the literature.